“SILVAMP TB LAM” rapid urine tuberculosis test predicts mortality in patients hospitalized with human immunodeficiency virus in South Africa - Sossen, Bianca; Denkinger, Claudia M. (Clinical infectious diseases, 2020)
Reducing diagnostic delay is key toward decreasing tuberculosis-associated deaths in people living with human immunodeficiency virus. In tuberculosis patients with retrospective urine testing, the point-of-care Fujifilm SILVAMP TB LAM (FujiLAM) could have rapidly diagnosed tuberculosis in up to 89% who died. In FujiLAM negative patients, the probability of 12-week survival was 86-97%.